2004
DOI: 10.1387/ijdb.041883sc
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic regulation of retinal ganglion cell synaptic connectivity: from axons and dendrites to synapses

Abstract: This review highlights important events during the morphological development of retinal ganglion cells (RGCs), focusing on mechanisms that control axon and dendritic arborization as a means to understand synaptic connectivity with special emphasis on the role of neurotrophins during structural and functional development of RGCs. Neurotrophins and their receptors participate in the development of visual connectivity at multiple levels. In the visual system, neurotrophins have been shown to exert various develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 135 publications
(218 reference statements)
3
70
0
Order By: Relevance
“…The morphology of ganglion cell dendrites continues to be modified by pruning mechanisms that persist long after initial synaptic contacts are formed in the visual system (Coombs et al; Huberman). The extent and form of the dendritic arbor is modulated within the retina by afferent input mediated through neurotransmitters produced by bipolar and amacrine cells (Cohen-Cory & Lom, 2004). As was observed in the present study, the cell densities of the inner nuclear layer that contains bipolar and amacrine cells, had significantly increased in the non-deprived eye with increasing duration of deprivation.…”
Section: Discussionsupporting
confidence: 83%
“…The morphology of ganglion cell dendrites continues to be modified by pruning mechanisms that persist long after initial synaptic contacts are formed in the visual system (Coombs et al; Huberman). The extent and form of the dendritic arbor is modulated within the retina by afferent input mediated through neurotransmitters produced by bipolar and amacrine cells (Cohen-Cory & Lom, 2004). As was observed in the present study, the cell densities of the inner nuclear layer that contains bipolar and amacrine cells, had significantly increased in the non-deprived eye with increasing duration of deprivation.…”
Section: Discussionsupporting
confidence: 83%
“…Optic axons in lower vertebrates express the cognate BDNF receptor, trkB, and tectum produces limited BDNF (4). Exogenous application of BDNF directly to axons during development promotes branching (3,4) and similar results have been obtained for regenerating fibers (Dawson and Meyer, unpublished).…”
Section: Number Of Fibers and Competitionsupporting
confidence: 69%
“…In the developing visual system, neurotrophins have been shown to exert various influences, from guiding the morphological differentiation of neurons to controlling the functional plasticity of visual circuits. BDNF contributes to the establishment and refinement of visual connectivity by acting at multiple levels in the visual pathway, from the retina to the visual cortex (von Bartheld, 1998;Hanover et al, 1999;Huang et al, 1999;Berardi et al, 2003;Cohen-Cory and Lom, 2004;Mandolesi et al, 2005). The spatial and temporal patterns of expression of BDNF and its high-affinity receptor TrkB are consistent with a role for BDNF in modulating visual circuit development.…”
Section: Introductionmentioning
confidence: 94%
“…Work in Xenopus has demonstrated that BDNF shapes the morphological differentiation of RGCs and their synaptic connectivity (Lom and Cohen-Cory, 1999;Alsina et al, 2001; Cohen-Cory and Lom, 2004;Du and Poo, 2004;Hu et al, 2005) and to a lesser extent affects the morphological and synaptic differentiation of postsyn-aptic tectal cells (Du and Poo, 2004;Sanchez et al, 2006). It remained to be determined, however, whether BDNF acts directly on RGCs or whether it influences both presynaptic and postsynaptic neurons to shape their synaptic connectivity.…”
Section: Introductionmentioning
confidence: 99%